Energy - Woodford, Chris; Cockburn, Dave (London : DK, 2007)
Full-color photographs and text explore energy; covering temperature, food, nuclear and solar power, fossil fuels, propulsion, and other related topics.
Includes index.
7.3
5-8.
5-8
Keywords: Force and energy -- Juvenile literature; Power resources -- Juvenile literature; Force and energy; Power resources; Energy resources; Force and energy